A rare case of metastatic carcinoma at the colostomy site after abdominoperineal resection - Manne, Dheeraj; Aroul, Tirou; Smile, Robinson (International Surgery Journal, 2025)
Metastatic carcinoma at the colostomy site after abdominoperineal resection is very rare and only a handful of case reports have been reported in literature. In this case, 40 years old woman who underwent abdominoperineal resection for rectal cancer presented a year later with stomal nodule and stricture. A portion of the colon with the mesentery, the stoma and the surrounding skin were excised and a new end stoma was created in the transverse colon. Biopsy revealed adenocarcinoma. A stomal nodule may be missed in follow up until the patient presents with symptoms. Stomal recurrence should therefore be considered whenever the patient presents with stomal nodule, ulceration, bleeding or obstruction